2018
DOI: 10.5217/ir.2018.16.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Enteric infections complicating ulcerative colitis

Abstract: Enteric infections have previously been postulated to play a role in the pathogenesis of inflammatory bowel disease (IBD), however, little evidence exists in the etiologic role of specific enteric infections in the development of IBD. When encountered in the setting of IBD, enteric infections pose a clinical challenge in management given the competing treatment strategies for infectious conditions and autoimmune disorders. Here we present the case of a young male with enteric infections complicating a new diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The current study particularly focused on the differences in the taxa at the genus level. A significantly higher proportions of the genus Turicibacter, Ruminococcaceae, and Lactobacillus were detected in the control group than those in DSS group, which was similar to previous research 22–24 , while a great abundance of the genera Klebsiella , Parabacteroides was observed in the DSS group, which was also validated by other studies 25,26 . Moreover, the administration of CRH further aggravated these changes in IBD (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The current study particularly focused on the differences in the taxa at the genus level. A significantly higher proportions of the genus Turicibacter, Ruminococcaceae, and Lactobacillus were detected in the control group than those in DSS group, which was similar to previous research 22–24 , while a great abundance of the genera Klebsiella , Parabacteroides was observed in the DSS group, which was also validated by other studies 25,26 . Moreover, the administration of CRH further aggravated these changes in IBD (Fig.…”
Section: Resultssupporting
confidence: 91%
“…28 In addition, there has been at least one case study suggesting the association of K. oxytoca with refractory colitis independent of antibiotic treatment. 29 The source of K. oxytoca infection often comes from the hospital environment 30 and as such may pose a danger to patients undergoing treatment, such as with K. oxytoca contamination upon intravenous injection causing septic arthritis. 31 Despite the emerging importance of K. oxytoca as a human pathogen, to the best of our knowledge, no studies on the interaction between this bacteria and T cells in colitis are available.…”
Section: Discussionmentioning
confidence: 99%